2010
DOI: 10.3201/eid1602.090900
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofCryptococcus gattii, British Columbia, Canada, 1999–2007

Abstract: Incidence is high, but the predominant strain does not seem to cause greater illness or death than do other strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
145
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(156 citation statements)
references
References 28 publications
10
145
1
Order By: Relevance
“…In regions like the Northern Territory in Australia, it has been reported that the mean annual incidence per million population was 6.6 and in New Zealand, of 2.2 (30), similar to the incidence reported in Colombia. The low incidence observed in HIV patients is consistent with reports describing the changing epidemiology of opportunistic infections in persons with AIDS (31). The fact that in Colombia the overall incidence of cryptococcosis among HIV patients has not changed significantly since 1997 may well be due to modifications in the management of HIV infection itself rather than to changes in environmental exposure to the fungus or to an increase in the virulence of the pathogen (16).…”
Section: Discussionsupporting
confidence: 85%
“…In regions like the Northern Territory in Australia, it has been reported that the mean annual incidence per million population was 6.6 and in New Zealand, of 2.2 (30), similar to the incidence reported in Colombia. The low incidence observed in HIV patients is consistent with reports describing the changing epidemiology of opportunistic infections in persons with AIDS (31). The fact that in Colombia the overall incidence of cryptococcosis among HIV patients has not changed significantly since 1997 may well be due to modifications in the management of HIV infection itself rather than to changes in environmental exposure to the fungus or to an increase in the virulence of the pathogen (16).…”
Section: Discussionsupporting
confidence: 85%
“…Similar observations were reported in PNG and were attributed to an increased exposure of males to environmental sources of C. gattii (209). On Vancouver Island, however, only 55% of the outbreak cases affected males, and in the Pacific Northwest, 54% affected males (132,198), suggesting that exposure is the predominant factor under these circumstances. Interestingly, 85% (21 of 25) of sporadic cases in the United States affected men (251).…”
Section: Epidemiology Of Human Infectionsupporting
confidence: 67%
“…VGII infections also occur but are, to date, geographically restricted to the Arnhemland region of the Northern Territory and the southwest of Western Australia (113,117). In contrast, clonal VGII subtypes (referred to as outbreak strains) of C. gattii caused case clusters in British Columbia (subtypes VGIIa and VGIIb) and in the Pacific Northwest (subtypes VGIIa, VGIIb, and VGIIc) (38,132,198,251); subtype VGIIc is a novel subtype not found outside the United States (68). Theories on how these VGII subtypes may have arisen in North America are discussed above (see Epidemiology, Origin, and Evolution, above).…”
Section: Epidemiology Of Human Infectionmentioning
confidence: 99%
See 2 more Smart Citations